Semantic Analysis of Prophet Muhammad's Letter to the Roman Emperor: A Study on the Message Content and Textual Meaning - Mufid, Miftahul; Diantika, Devi Eka (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2024)
Surat Nabi Muhammad kepada Raja Romawi, Heraclius, adalah salah satu dokumen bersejarah yang memiliki relevansi besar dalam konteks studi keislaman dan sejarah dunia. Penelitian ini melakukan analisis semantik terhadap teks surat tersebut dengan tujuan untuk mengungkap pesan dan makna yang terkandung di dalamnya. Metodologi penelitian melibatkan pengumpulan teks asli dalam bahasa Arab, terjemahan ke dalam bahasa yang dapat dimengerti, identifikasi struktur bahasa dan gaya penulisan, analisis semantik, pemahaman konteks sejarah dan budaya, serta perbandingan dengan teks-teks lain yang relevan. Hasil penelitian mengungkapkan bahwa Surat ini mencerminkan identitas dan budaya Nabi Muhammad dan umat Islam melalui penggunaan bahasa Arab dan salam yang penuh rasa hormat. Identitas pengirim surat sebagai "hamba Allah dan utusanNya" menggambarkan kerendahan hati Nabi Muhammad dan perannya sebagai utusan Allah. Surat ini mengandung ajakan untuk memeluk Islam, dengan menekankan pahala besar bagi penerima yang menerima dan konsekuensi serius bagi penolaknya. Pengakuan monoteisme dalam surat menunjukkan keyakinan kuat dalam ajaran Islam, sementara penggunaan kata "saksikanlah" menguatkan kekuatan dan undangan universal dalam ajaran tersebut. Penelitian ini juga menyoroti pentingnya pemahaman konteks sejarah dan budaya pada saat surat itu ditulis, termasuk situasi politik dan sosial serta hubungan antara komunitas Muslim dan Kekaisaran Romawi Timur. Dengan demikian, penelitian ini memberikan wawasan yang mendalam tentang pesan dan makna Surat Nabi Muhammad kepada Raja Romawi dalam konteks sejarah awal Islam dan diplomasi antarperadaban, menjadikannya bagian penting dari sejarah Islam dan dakwah Nabi Muhammad.  The letter from Prophet Muhammad to the Roman Emperor Heraclius is one of the historical documents of great significance in the context of Islamic studies and world history. This research conducts a semantic analysis of the text of the letter with the aim of uncovering the messages and meanings it contains. The research methodology involves collecting the original text in Arabic, translating it into understandable languages, identifying language structures and writing styles, semantic analysis, understanding the historical and cultural context, and comparing it with relevant texts. The research findings reveal that the letter reflects the identity and culture of Prophet Muhammad and the Islamic community through the use of the Arabic language and a respectful greeting. The identity of the sender as a "servant of Allah and His messenger" illustrates the humility of Prophet Muhammad and his role as a messenger of Allah. The letter contains an invitation to embrace Islam, emphasizing great rewards for those who accept it and serious consequences for those who reject it. The acknowledgment of monotheism in the letter demonstrates a strong belief in Islamic teachings, while the use of the phrase "bear witness" reinforces the power and universal invitation of these teachings. This research also highlights the importance of understanding the historical and cultural context in which the letter was written, including the political and social situation and the relationship between the Muslim community and the Eastern Roman Empire. Therefore, this research provides deep insights into the messages and meanings of Prophet Muhammad's letter to Emperor Heraclius in the context of early Islamic history and intercivilizational diplomacy, making it an essential part of Islamic history and the Prophet Muhammad's mission.